Flow diagnostics essential code: A simple and brief format for the summary of leukemia phenotyping. Issue 4 (25th November 2013) - Hrušák, Ondřej; Basso, Giuseppe; Ratei, Richard; Gaipa, Giuseppe; Luria, Drorit; Mejstříková, Ester; Karawajew, Leonid; Buldini, Barbara; Rozenthal, Eti; Bourquin, Jean Pierre; Kalina, Tomáš; Sartor, Mary; et al.
<x xml:space="preserve">Abstract</x> Background Flow cytometry is a valuable part in the routine diagnostics of acute leukemia (AL). Although internationally recognized definitions of main AL subsets are available, there is currently no consensus format for the short summary of clinical flow cytometry reports. Since clinical reports are too long for most database purposes, there is a need for a standardized format of their short summaries. Methods The Associazione Italiana Ematologia Oncologia Pediatrica—Berlin Frankfurt Muenster (AIEOP‐BFM) Flow Network that encompasses reference diagnostics laboratories in Australia, Austria, Czechia, Germany, Israel, Italy, and Switzerland have designed a pro‐forma for the summary of flow cytometry results in the diagnosis of leukemia. The process involved several meetings and other communications, during which the group established a consensus on the essentials that lead to the diagnostic conclusions in childhood AL. Results The "Flow Diagnostics Essential (FDE) Code" is a result from an agreement within the AIEOP‐BFM Flow Network. In a standardized format, it reports the extent of the infiltration by a malignant clone, followed by description antigen expression as strong, weak or negative, and a diagnostic conclusion. Conclusions A consensus brief format (the "FDE Code") has been designed as a brief summary of the diagnostic immunophenotype of childhood AL. It is also applicable for the diagnostic investigation of other malignancies by flow cytometry. The FDE code may be included in the final clinical report and/or used in the setting of a multicenter clinical trial database. © 2013 International Clinical Cytometry Society